Review of Active Compounds from Medicinal Plants with Antihyperglycemic Efficiency on Translocation and Expression of Glucose Transporter 4 on Muscle and Adipose Tissue - Widyasti, Jena Hayu; Kurniasari, Fitri; Nugroho, Rahmat Budi (Asian Journal of Pharmaceutical Research and Development, 2022)
Glucose transporter’s mechanism is influenced by the presence of insulin, especially GLUT4 which acts on muscle, adipose, and brain tissue. Medicinal plants with active compounds that were able to regulate the expression and translocation of GLUT helps in the treatment of insulin resistance and hyperglycemia. This study aimed to determine which active compounds isolated from medicinal plants have antihyperglycemic activity on GLUT4 expression in muscle and adipose tissue. The research method used was by searching the literature electronically with the keywords "Plant Isolation", "Chemical Compounds", "Antihyperglycemic Activity", and "Glucose transporter (GLUT) 4". Literature sources in the form of international and national journals have been found on several sites, such as NCBI, Elsevier and Pubmed, and others. A literature search in the form of selected journals from 2016 to 2021. The data were analyzed using the PRISMA (Prefered Reporting Items for Systematic Review and Meta-analyses) method. The results showed that the active substances contained in the plant have antihyperglycemic activity by increasing the translocation and expression of GLUT4 in skeletal muscle cells, adipocytes, and tested-animal models of DM.